Virtual full-duplex multiple-input multiple-output relaying in the presence of inter-relay interference - Igbafe Orikumhi, 1983- , author 607260; Leow, Chee Yen, supervisor 459995; Fakulti Kejuruteraan Elektrik 540663 (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2017)
Thesis (Ph.D (Kejuruteraan Elektrik))